Non-Kasha phosphorescence: the role of azulene and carbazole. - Díaz-Fernández, Marcos; Marín-Beloqui, José Manuel; Junzhi, Liu; Casado-Cordón, Juan (My University, 2024)
Organic electronics have the capabilities to replace inorganic semiconductors in electronic devices. Hence, it is important to pay attention to organic molecular structure, i.e. π conjugation and aromaticity, to achieve these goals. Spectroscopy represents the perfect tool to study the electronic properties of these molecules to help us to know their structure-property relationship. Azulene is an electronic isomer of naphthalene which is described as a zwitterion-like aromatic structure. Azulene is composed to a 7-member ring fused to a 5-member ring and the main interest in azulene-based derivatives is their ability to violate the Kasha photoemission rule. According to Kasha´s rule, the photoemission always occurs from the lowest energy excited state. However, Azulene-based molecules have previously shown emission from S2 and S3 excited states. Despite the large interest of the non-Kasha emission, the relationships between molecular structure and this anti-Kasha emission has not been well stablished. In this work, we have studied several novel structures based on azulene with different spectroscopic techniques, such as low temperature absorption and emission, Raman and transient absorption spectroscopy to elucidate the requirements for this non-Kasha emission to occur in these azulene-based molecules.
Elucidating non-Kasha emission structure-property relationship in azulene-based molecules.
Keywords: Fosforescencia; Fotoquímica; Espectroscopía; Azulene; Phosphorescence; Carbazole; Non-Kasha emission